Determinants of Poverty in Surakarta - Asida Wahyu Hidayat; Nur Hidayah (www.amertainstitute.com, 2023)
This study aims to determine the factors that affect poverty in the city of Surakarta. This type of research is quantitative using multiple linear regression analysis methods with Ordinary Least Square (OLS) approach. Thisstudy uses time series data from 2002-2021. The variables used in this study are population, Gross Regional Domestic Product, inflation, unemployment, and Human Development Index in Surakarta city from 2002-2021. The test results showed that population and unemployment significantly affect the level of poverty. HDI and GDPnegatively affect poverty levels. Inflation has no effect on poverty. The implication of the test results is the unresolved problem of poverty in the city of Surakarta from 2002-2021. Policies that need to be done are to createa family planning program to stabilize the population, maximize productivity and resources to increase GDP and HDI, and expand employment to reduce unemployment in the city of Surakarta.